Penerapan Metode Pembelajaran Berbasis Proyek dalam Meningkatkan Keterampilan Abad 21 di SMPN 3 Tanjung Medan - Patimah, Siti; Sumardi, Sumardi; Iskandarsyah, Iskandarsyah (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to analyze the effectiveness of implementing project-based learning methods in enhancing 21st-century skills among students at SMPN 3 Tanjung Medan. 21st-century skills, such as critical thinking, creativity, communication, and collaboration, are essential aspects that need to be developed in the learning process. The research method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which consists of two cycles with stages of planning, implementation, observation, and reflection. The research subjects were eighth-grade students who experienced difficulties in developing critical thinking and teamwork skills in learning. Data were collected through observation, skill tests, interviews, and documentation. The research findings indicate that the implementation of project-based learning significantly improves students' critical thinking, creativity, communication, and collaboration skills. In the first cycle, students began to engage in discussions and problem-solving, although there were still challenges in group coordination. In the second cycle, there was a more substantial improvement, where students became more active in discussions, developed innovative ideas, and effectively collaborated in completing projects. Data analysis showed an increase in students' average 21st-century skill test scores from the first to the second cycle. Additionally, interviews with teachers and students revealed that this method provided a more engaging and challenging learning experience, motivating students to participate more actively in lessons. The success of this method was supported by the teacher's role as a facilitator, the use of relevant projects, and the application of reflective strategies in each learning cycle. The conclusion of this study is that project-based learning is effective in enhancing students' 21st-century skills at SMPN 3 Tanjung Medan. The study implies the need for further development of more varied project designs and teacher training to optimize the implementation of this method. Thus, the results of this study can serve as a reference for the development of innovative learning strategies that encourage students to become active and independent learners.